The effects of behavioral intervention on anthropometric, clinical, and biochemical parameters in patients with polycystic ovary syndrome: a systematic review and meta-analysis - Xie, Min; Yang, Yang; Zhang, Jing (Frontiers in Endocrinology, 2024)
Objective: To evaluate the effects of behavioral intervention for polycystic ovary syndrome (PCOS).Methods: Electronic databases were searched, including Pubmed, Medline, EMBASE, and the Cochrane Central Register of Controlled Trials from inception to 1 April 2023. Inclusion criteria for this study required a diagnosis of PCOS.compared with routine treatment. The studies included in the analysis were designed as randomized controlled trials (RCTs). We conducted meta-analyses following the recommended guidelines. The data was analyzed using either the random effects model or fixed effects model. The results of the studies were expressed as either mean differences (MD) or standardized mean differences (SMD) along with their corresponding 95% confidence intervals (CIs).Results: Eight RCTs were identified, including data from 744 patients (415 in the intervention group and 329 in the control group). The results indicate an improvement in the effectiveness of behavioral interventions for weight loss (MD: -1.07; 95% CI: -2.1 to 0.03; I 2 =0%; P=0.04), body mass index (BMI) (MD: -1.12; 95% CI: -1.92 to -0.33; I 2 =73%; P=0.006), waist circumference (MD: -3.97; 95% CI: -5.64 to -2.29; I 2 =0%; P<0.00001), quality of life about weight (MD: 0.58; 95% CI: 0.15 to 1.02; I 2 =0%; P=0.008), depression (SMD: -1.12; 95% CI: -2.35 to -0.07; I 2 =92%; P=0.04), and triglycerides (MD: -0.16; 95% CI: -0.27 to -0.05; I 2 =27%; P=0.004). However, there were no significant differences in menstrual cycles, hirsutism, emotions, and infertility. The study also found that behavioral interventions had no significant effect on systolic and diastolic blood pressure, high-density lipoprotein, low-density lipoprotein, homeostasis model assessment of insulin resistance, testosterone, total cholesterol, fasting glucose, fasting insulin, hemoglobin A1C, and sex hormone binding globulin.: Behavioral intervention supplementation contributes to weight loss, reduction in BMI and waist circumference, and improvement in depression among patients with PCOS. However, no significant improvement was observed in the biochemical index and quality of life. The long-term effects of behavioral intervention for PCOS remain unclear due to limitations in the quality of the studies involved and the short duration of treatment.